2006
DOI: 10.1038/sj.ijo.0803403
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial response of trans fatty acids in prepubertal obese children

Abstract: Objectives: To evaluate the intake, plasma concentrations and postprandial response of trans fatty acids in obese and control children at prepubertal age in order to detect potential associations with childhood obesity. Design: Case-control study, clinical dietary intervention with a 428 kcal standardized breakfast and longitudinal 3 h postprandial follow-up for trans fatty acid plasma levels. Subjects: Fifty-four children aged 6-13 years of both sexes, 34 obese (body mass index 497th percentile for age and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…We previously reported that this group of obese children had a significant higher absolute daily intake of energy and all major nutrients compared with normal-weight children but the intake of energy and macronutrients to BMI ratios were significantly lower in the obese group [11]. No differences in the daily intake of energy and macronutrients as well as saturated, monounsaturated and polyunsaturated fat, were observed between the obese NMS and MS groups ( Table 2).…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…We previously reported that this group of obese children had a significant higher absolute daily intake of energy and all major nutrients compared with normal-weight children but the intake of energy and macronutrients to BMI ratios were significantly lower in the obese group [11]. No differences in the daily intake of energy and macronutrients as well as saturated, monounsaturated and polyunsaturated fat, were observed between the obese NMS and MS groups ( Table 2).…”
Section: Resultsmentioning
confidence: 46%
“…Two recent papers by our group on the postprandial response of trans and other plasma fatty acids in the prepubertal obese children are based on the same population of the present report [11,12]. The study was approved by the Human Investigation and Ethics Committees of the University of Granada and the Reina Sofia University Hospital of Cordoba (Spain).…”
Section: Methodsmentioning
confidence: 96%
“…TFA intake and plasma TFA was not significantly different between a group of 34 obese children (497 BMI percentile for age and sex) and 20 normal-weight controls. 32 The mean intake for both groups was o1 g TFA per day, and the adjustment included no apparent adjustment for either lifestyle or diet. A study in morbidly obese (BMI 440 kg m 2 ) and non-obese (BMI o30 kg m 2 ) Brazilian subjects also showed no correlation between BMI and TFA levels in adipose tissue, but, once again, there was no apparent adjustment for confounding factors.…”
Section: Human Studiesmentioning
confidence: 99%
“…31,32 Care must be taken when estimating TFA intake based on reported food intake, as it has been shown that different brands of food products can result in considerable variation in TFA content for the same diet -as much as 1.4-25.4 g day À1 in one example compiled in 1999. 33 There has been significant reduction in TFA content of most foods over the past decade, 13 and so it is important that composition databases have been updated to take this into account.…”
Section: Human Studiesmentioning
confidence: 99%
“…There have been several cross-sectional studies carried out in Spain on childhood obesity that have allowed us to know the prevalence and its related factors, but there are few case-control design studies to determine factors with association (4)(5)(6) . One of them (7) suggests that physical leisure-time activity, a family history of obesity, watching television (TV) and sugar-sweetened beverage consumption are important predictive variables for childhood obesity.…”
mentioning
confidence: 99%